ECO-THEOLOGY AND THE PARADOX OF CHRISTIAN ENVIRONMENTALISM IN ALEXIS M. SMITH’S MARROW ISLAND - Hodge, Cr Patricia Mary (ShodhGyan-NU: Journal of Literature and Culture Studies, 2025)
Alexis M. Smith’s novel Marrow Island (2016) is an eco-thriller set in the aftermath of an environmental catastrophe that tests the fragility of the relationship between humankind and the environment. Rooted in the discourse of eco-theology, this paper analyses how the novel critiques mainstream Christian tradition’s perspectives on nature while proposing an alternative eco-spiritual vision. The novel portrays an eco-theological movement that seeks to remediate the land but cannot escape the entanglement from the hierarchical anthropomorphic positioning of humans over nature. Through this analysis, the paper adds to discussions on the viability and implications of eco-theology within Christianity. The paper thus situates Marrow Island within a broader critique of Christianity’s anthropomorphism and exposes the limitations of the expectations of easily integrating environmentalism within religious frameworks.